التحكيم وفقًا لاتفاقية الأمم المتحدة بشأن نقل البضائع عن طريق البحر (هامبورغ، 1978) - Ghassan, ali; Haidara, jaber (Tishreen University journal of research and scientific studies -economic and legal sciences, 2024)
International maritime transport represents the backbone of international trade in our current era, for many reasons, such as low costs and the ability to transport large quantities of goods at once. The United Nations Convention on the Maritime Transport of Goods of 1978, known as the Hamburg Convention, represents a qualitative shift in regulating the rules of maritime transport of goods. Among the important topics regulated by the agreement is the subject of arbitration, as it is the most important means of settling disputes related to international trade contracts, especially the contract for the maritime carriage of goods. Accordingly, this research studies the rules of the Hamburg Convention related to arbitration as a means of settling disputes related to the contract for the maritime carriage of goods. يمثل النقل البحري الدولي عصب التجارة الدولية في عصرنا الحالي، ألسباب عديدة كانخفاض التكاليف والقدرة عمى والمعروفة 1978 نقل كميات كبيرة من البضائع دفعة واحدة، وتمثل اتفاقية األمم المتحدة لمنقل البحري لمبضائع لعام ىامبورغ، نقمة نوعية عمى صعيد تنظيم قواعد النقل البحري لمبضائع، ومن بين الموضوعات اليامة التي باسم اتفاقية نظمتيا االتفاقية، موضوع التحكيم، باعتباره أىم وسائل تسوية النزاعات المرتبطة بعقود التجارة الدولية، وخاصة عقد د اتفاقية ىامبورغ المتعمقة بالتحكيم كوسيمة لتسوية النزاعات النقل البحري لمبضائع، وبناء عميو يتناول ىذا البحث قواع ال
Keywords: Arbitration; Bill of lading; Bills of lading; Carriage of Goods by Sea (1978); Hamburg Convention; Hamburg Rules; International commercial arbitration; Maritime carriage contract; Maritime transport; UN Convention; اتفاقية ىامبورغ; التحكيم; سند الشحن; عقد النقل البحري

The Pros and Cons of Third Party Funding in the International Investment Arbitration Regime - Mirveisi, Alireza; Zakerian Amiri, Mehdi; Abdollah Zadeh, Mohammad Ali (Public Law Researsh, 2023)
There is a growing stream of critics who see investment arbitration in favor of foreign investors and as a negative force as opposed to sustainable development. The phenomenon of third-party funding and its use in investment arbitration has increased such concerns. Third-party funding is basically the payment of all or a part of the arbitration costs of one of the parties of dispute by a third party funder which in return, the funder receives a percentage of the output of the award if successful. The purpose of this article is to explain and analyze the theoretical differences between pros and cons of third-party funding regarding the access to justice, screening mechanism for the claims, and the financial consequences on the host state. In this article, the advocates see third-party funding as a means of access to justice for aggrieved investors in investment claims, while the adversaries refering on the profitability of third-party funding, see this method in arbitration a form of wealth transfer from public sector to private corporations and also refer to the asymmetric structure of the investment arbitration regime as well as the risks arising from the transfer of management and control of arbitration process to the third party funders. یک جریان رو به رشدی از منتقدان وجود دارد که داوری سرمایه‌گذاری را به نفع سرمایه‌گذاران خارجی و بعنوان یک نیروی منفی در تضاد با توسعه پایدار می‌داند. پدیده تأمین مالی ثالث و بکارگیری آن در داوری سرمایه‌گذاری به این نگرانی‌ها افزوده است. تأمین مالی ثالث اساساً پرداخت تمام یا بخشی از هزینه‌های داوری یکی از طرفین دعوی توسط تأمین کننده شخص ثالث است که در ازای آن، تأمین کننده مالی درصدی از رأی صادره را در صورت پیروزی دریافت می‌نماید. هدف مقاله، تشریح و تحلیل اختلافات نظری موافقان و مخالفان تأمین مالی ثالث در خصوص دستیابی به عدالت، غربالگری دعاوی و تبعات مالی آن بر دولت است. در این مقاله موافقان، تأمین مالی ثالث را ابزاری جهت دستیابی به عدالت برای سرمایه‌گذاران زیان‌دیده در دعاوی سرمایه‌گذاری در نظر می‌گیرند در حالی که مخالفان با اتکا به اهداف سودآوری تأمین مالی ثالث، این روش را در داوری نوعی انتقال ثروت از بخش عمومی به بخش خصوصی می‌دانند و به ساختار نامتقارن رژیم داوری سرمایه‌گذاری و خطرات ناشی از انتقال مدیریت و کنترل فرایند داوری به تأمین کنندگان شخص ثالث نیز اشاره می‌نمایند.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitragem; Arbitration; Investment Arbitration Regime; Investments; Screening Mechanism for Claims; Third Party Funding; تأمین مالی ثالث; دستیابی به عدالت; رژیم داوری سرمایه‌گذاری; غربالگری دعاوی

The Unilateral Arbitration Clause between Permissibility and Nullity - Mahmoud Jaradat, Nashat; JassimSarhan, Ghassan (Information Sciences Letters, 2022)
Researching the judicial applications of Arab countries to one of the issues that have occupied legal thoughts in the Western world for decades and still in one form or another, the so-called Unilateral Arbitration Clauses, we did not find a discussion of the applicability of this clause within the laws. Even though this condition takes a reasonable space of the legal arguments as previously mentioned, it has even become widely used in contracts, such as tenancy, contracting, and financial investments. The study showed that the above-mentioned clause has recently increased its use in financing contracts, especially with the increasing globalization of banking services and bank transfers. Although banks usually prefer to resort to traditional litigation, lack of similarity in the legal rules and judicial applications related to banking transactions and their difference from one country to another was a reason for the banks preference of resorting to arbitration. There is no examination of the legitimacy of an unequal or optional arbitration clause in Bahrain. Also, the Bahraini and Egyptian courts, to the best of our knowledge, did not decide whether it should be considered null or valid. The same case is applied to the French courts which have no cases that examined this type of clauses except for a case in 2006 and the other is a judgment close to the same issue on October 7, 2015, from the French Court of Cassation. The English and American courts were different; they examined this clause and had several judicial implementations due to the fact that most of the arbitration terms are either related to multinational companies operating within the framework of the Wall Street Stock Exchange in New York or those that stipulate the enforcement of British and Wales law on the provisions of the contract . However, many Arab countries, in general, as well as Bahrain and some Gulf countries, in particular, are seeking in their economic model to attract foreign investments and capital, especially those related to financial and banking industries, to diversify sources of income. The decision of investing or not investing the capital in a country is made by the judicial authority in terms of independence as well as the judicial application of legal texts as these factors are directly reflected in the desire to invest and show the possibility of protecting investors.

Settlement of Disputes Arising from Documentary Credit Under National and International Regulations - Nour, Hoda Magdy (UAEU Law Journal, 2022)
The need Settlement of disputes arising from bank credit between national and international rules, protecting the interests of the bank and ensuring its financial rights before the debtor. As the Bank faces different technical and legal difficulties, as well as the multiplicity of legal adaptation, we deal with the rules governing banking accreditation from the point of pleadings law, and the methods of amicable settlement of these disputes and following, and compulsory execution. International efforts are taking the lead in establishing the technical regulation of bank accreditation and setting rules "DOCDEX" in 1997, and the 2015 amendments, which still need more as they do not provide a legal way to implement them. It is necessary to find out legal regulation at the domestic and international levels, which calls for the legislator to intervene to organize its rules and procedures. We have sought in this study to weave the legal entity to seize bank credit within the legally acceptable limits based on a system of seizure of the debtor with third parties against the background of the legal system of documentary credit and the relationships arising from it, and its financial and economic effects that go beyond the parties to the beneficiaries of companies, bodies, and economic institutions, As the matter still requires the existence of special legislation regulating the seizure of bank credit, to ensure the effectiveness of the guarantees surrounding the appropriations by the national legislator and at the international level. This would expand the insurance of bank credit so that the creditors recover their full right directly or by seizing the value of the credit, which calls for organizing this seizure with rules that consider the privacy of this seizure and its rules and are consistent with the required speed in such transactions in a way that protects the creditor from abuse, in a manner that ensures the observance of confidentiality, due process, and the spirit of banking work, anticipate the possible future that will witness the decline of documentary credit and replace it with electronic transactions, the establishment of specialized banking courts that save time and effort.

The Right to Water in Investment Treaty Arbitration and Its Impact on Jurisdiction and Applicable Law - Geravand, Farshad (Public Law Researsh, 2022)
The right to water in investment arbitration has been one of the most contentious issues before investment arbitration tribunals in recent decades. The privatization of public services, including water and sanitation, and assigning them to foreign investors has caused the right to water as a vital benefit being repeatedly raised in investment arbitrations. However, due to tribunals’ narrow interpretation of jurisdiction and applicable law, this fundamental human right has been considered irrelevant and ignored, and this has fueled the legitimacy crises in investment arbitration. This research seeks to indicate the potentiality of more protection of the right to water through balancing the states international obligations in the two areas of investment law and human rights law. Proposed methods for integrating human rights with investment law include the correct interpretation of jurisdictional clauses and the applicable law based on the treaties interpretation principles, systematic integration and the inclusion of new clauses in investment agreements. طرح حق بر آب در داوری سرمایه‌گذاری یکی از مناقشه‌انگیزترین مباحث پیش روی دیوان‌های داوری در چند دهه اخیر بوده است. خصوصی‌سازی خدمات عمومی از جمله آب و فاضلاب و سپردن آنها به سرمایه‌گذاران خارجی موجب شده تا حق بر آب بعنوان یک منفعت عمومی و حیاتی بارها در داوری‌های سرمایه‌گذاری مطرح شود. با تفسیر مضیق محاکم از شروط صلاحیتی و قانون حاکم، این حق بنیادین بشری در برخی موارد نامربوط و نادیده تلقی شده و این امر به بحران مشروعیت در داوری سرمایه‌گذاری دامن زده است. این جستار می‌کوشد تا امکان حمایت بیشتر از حق بر آب را از طریق برقراری تعادل بین تعهدات بین‌المللی دولت‌ها در دو عرصه حقوق سرمایه‌گذاری و حقوق بشر نشان دهد و در پایان روش‌هایی را برای ادغام این دو از جمله تفسیر درست شروط صلاحیتی و قانون حاکم با تکیه بر اصول تفسیر معاهدات، تلفیق سیستمیک و گنجاندن بندهای جدید در موافقتنامه‌های سرمایه‌گذاری پیشنهاد کند.
Keywords: Applicable law; International Investment Arbitration; Jurisdiction; Right to Water; Systemic Integration; تلفیق سیستمیک; حق بر آب; داوری سرمایه‌گذاری بین‌المللی; شروط صلاحیتی; قانون حاکم

Role of Abuse of Rights Doctrine and Investment Arbitration Ratione Temporis in Limiting Nationality Planning - Saeedi, Niloofar; Askary, Pouria (Public Law Researsh, 2022)
Sometimes foreign investors after the dispute have arisen or when it is predictable and with the intention of bringing the dispute to arbitration, change their nationality or acquire new nationality. The phenomenon called Nationality Planning eases foreign investors’ access to a desirable treaty and increases the chance of bringing disputes against host states.So host states try to avoid these disputes by raising objections to Ratione Temporis or claiming abuse of rights. Arbitration tribunals’ approach towards their Ratione Temporis and abuse of rights is material in host states’ success in limiting Nationality Planning. So the question to be answered is that what requirements are considered by arbitrations in determining Ratione Temporis and abuse of rights and how these two are different. Arbitral precedent shows that these tribunals make distinction between cases of nationality planning contrary to their Ratione Temporis and cases that are considered as abuse of rights. However, in practice their strict approach results in limited acceptation of objections to Ratione Temporis or abuse of rights claims. گاه سرمایه‌گذار خارجی پس از بروز اختلاف یا زمانی که اختلاف قابل پیش‌بینی است و به قصد طرح دعوی در مرجع داوری، اقدام به تغییر تابعیت یا کسب تابعیت جدید می‌نماید. این اقدام که برنامه‌ریزی تابعیت نام دارد، دسترسی سرمایه‌گذار خارجی به یک معاهده سرمایه‌گذاری مطلوب را تسهیل کرده و احتمال طرح دعوی علیه دولت میزبان را افزایش می‌دهد. از این‌رو دولت‌های میزبان تلاش می‌کنند با طرح ایراد به صلاحیت زمانی یا سوء استفاده از حق، مانع پذیرش چنین دعوایی شوند. رویکرد مراجع داوری در احراز صلاحیت زمانی خود و تشخیص موارد سوء استفاده از حق، در موفقیت یا عدم موفقیت دولت میزبان در مقابله با برنامه‌ریزی تابعیت تعیین‌کننده است. بنابراین باید به این پرسش پرداخته شود که مراجع داوری چه شرایطی را برای احراز صلاحیت زمانی و سوء استفاده از حق در نظر می‌گیرند و چگونه میان این دو تمایز قائل می‌شوند. رویه مراجع داوری حاکی از آن است که این مراجع میان مواردی از برنامه‌ریزی تابعیت که مانع صلاحیت زمانی آن‌هاست و مواردی که سوء استفاده از حق تلقی می‌گردد، تمایز قائل می‌شوند. هرچند رویکرد سخت‌گیرانه آنها در عمل موجب می‌شود تنها در موارد محدودی ایراد به صلاحیت زمانی یا ادعای سوء استفاده از حق مورد پذیرش واقع شود.
Keywords: Abuse of rights; Bilateral Investment Treaty; Foreign Investment Arbitration; Nationality Planning; Ratione Temporis; برنامه‌ریزی تابعیت; داوری سرمایه‌گذاری خارجی; سوء استفاده از حق; صلاحیت زمانی; معاهده دوجانبه سرمایه‌گذاری

Third Party Investment in International Commercial Arbitration - Ebrahimi, Seyed Sadegh; Boloori, Peyman; Solhchi, Mohammad Ali (Public Law Researsh, 2022)
International commercial arbitration imposes heavy costs to the parties involved. In this regard, one of the new phenomena in international commercial arbitration is "financing of court costs by a third party investor. There are several reasons for the emergence of a third party investor: 1- involved parties may not have the resources to pay for the costs of arbitration or they may be reluctant to use their funds to finance the litigation: 2. the uncertainty of receiving compensation as a result of paying the arbitration fees might encourage the parties to transfer this risk to a third party; 3. having its own advantages and disadvantages. Since the funder holds the power of the purse, TPF entails the risk of the control of the claim being transferred to the third party funder. We might ask whether international arbitration tribunals should examine the extent of the investor's influence in determining the allocation of costs or not. In addition, is it essential to disclose the third parties contracts confidential? Overall, it is concluded that those mentioned Tribunals should allocate and guarantee the arbitration cost and agree on disclosing of third parties fund contracts under urgent conditions by international arbitration tribunal. مراجعه به داوری تجاری بین المللی هزینه های کلانی را برای طرفین درگیر در فرآیند داوری به همراه دارد و تأمین این هزینه ها در خیلی از موارد به‌صورت مانع در مراجعه به داوری نمود پیدا می‌کند. در همین راستا یکی از پدیده‌های جدید در داوری تجاری بین المللی، «تأمین مالی هزینه دادرسی توسط سرمایه گذار ثالث» است. ظهور سرمایه گذار ثالث دلایل متعددی دارد؛ اولاً طرفین دعوی ممکن است فاقد امکانات مالی کافی برای هزینه های داوری باشند، ثانیاً ممکن است طرفین دعوی تمایلی به استفاده از منابع مالی خود برای تأمین مالی دادرسی پرهزینه نداشته باشند، ثالثاً عدم قطعیت ذاتی که در زمینه امکان اخذ خسارت در نتیجه دادرسی وجود دارد می تواند باعث تمایل طرف منازعه به انتقال این ریسک به شخص ثالث شود. پرسش این است که آیا محاکم تجاری بین‌المللی تعیین تخصیص هزینه‌ها بپردازد یا خیر؟ و آیا افشاسازی قراردادهای شخص ثالث ضروری می‌باشد؟ در نهایت این نتیجه حاص می‌شود که محاکم مذکور باید به تعیین تخصیص و تضمین هزینه‌های داوری پرداخته و از سویی با افشاسازی قراردادهای تامین مالی شخص ثالث در داوری تجاری بین المللی، در شرایط خاص و ضروری موافقت نمایند.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Cost Allocation; Disclosure; International Arbitration Tribunals; International commercial arbitration; Investments; Third Party Investment; Third parties; افشاسازی; تخصیص هزینه‌ها; داوری تجاری بین‌المللی; دیوان‌های داوری بین‌المللی; سرمایه‌گذاری شخص ثالث

A Legal Analysis of the Structure of Dispute Resolution Mechanisms of International Tax Agreements - Salehifar, Alireza (Public Law Researsh, 2022)
As international trade is expanding, international trade and tax disputes are increasing. Under international tax agreements, there are two mechanisms for the resolution of potential disputes between contracting States. These agreements mostly rely on a form of negotiation known as the “Mutual Agreement Process (MAP)” as the main mechanism for the settlement of disputes. During the last decade, the inclusion of “ad hoc arbitration” as a new dispute resolution mechanism in international tax treaties has become popular to augment the MAP. Iran has long concluded several international tax agreements with several countries for the avoidance of double taxation. Due to Iran’s macroeconomic policy for relying more on tax revenues as an alternative to revenues from the petroleum industry, it is important that the Iranian lawyers seek to focus more on tax law and tax dispute resolution mechanisms. The purpose of this article is to introduce and critically analyse the dispute resolution mechanisms of international tax agreements. In this article, to make some suggestions for the improvement of the dispute resolution system of tax treaties, the strengths and weaknesses of the MAP and ad hoc arbitration, will be scrutinised by adopting a descriptive-analytical approach. همسو با گسترش تجارت فراسرزمینی،‌ میزان دعاوی مرتبط با تجارت و مالیات‌های بین‌المللی نیز افزایش یافته است. در بسیاری از معاهده‌های مالیاتی بین‌المللی برای حل اختلافات، دو ساز و کار با عنوان «فرآیند توافق دوجانبه» و «داوری موردی» وجود دارد. فرآیند توافق دوجانبه که مبتنی بر مذاکره بین طرفین معاهده است بعنوان ساز و کار اصلی و داوری موردی هم که در یک دهه اخیر در این معاهده‌ها رواج یافته، بعنوان ساز و کار مکمل فرآیند توافق دوجانبه برای حل اختلافات استفاده می‌شوند. ایران از دیرباز جهت اجتناب از مالیات مضاعف، معاهده‌های مالیاتی متعددی را با کشورهای مختلف منعقد نموده است. همچنین سیاست کلان اقتصادی کشور در سال‌های اخیر مبتنی بر اتکای بیشتر به درآمدهای مالیاتی بعنوان جایگزینی برای درآمدهای نفتی بوده است. لذا اهمیت شناخت این نوع معاهده‌ها و‌ مکانیسم‌های حل و فصل اختلافات آنها برای حقوقدانان کشور بیش از پیش آشکار می‌شود. هدف این مقاله معرفی،‌ تحلیل و نقد ساز و کارهای موجود در معاهده‌های مالیاتی بین‌المللی برای حل اختلافات می‌باشد. در این مقاله نقاط ضعف و قوت فرآیند توافق دوجانبه و داوری موردی به شیوه توصیفی-تحلیلی بیان و راهکارهایی جهت بهبود این مکانیسم‌ها ارائه می‌شود.
Keywords: Arbitrage; Arbitragem; Arbitration; Dispute Resolution; International Tax Agreements; Mutual Agreement Procedure (MAP); Negotiation; داوری; فرآیند توافق دوجانبه; مذاکره; معاهده مالیاتی بین‌المللی; ‌ حل و فصل اختلاف

الحق المعنوي للفنان العازف أو المؤدي في قانون الملكية الأدبية والفنية - دراسة مقارنة - - بعديد, دلال (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
يعتبر الفنان العازف أو المؤدي، الطائفة الوحيدة من أصحاب الحقوق المجاورة التي تتمتع بحقوق معنوية ومالية على أعماله. فالطابع الإبداعي الذي يكتسيه أداؤه يبرز شخصيته الأدبية والفنية، على خلاف أعمال أصحاب الحقوق المجاورة التي تتسم بالطابع الصناعي اولمادي. يتضمن الحق المعنوي جملة من الصلاحيات تمكن الفنان من الاستفادة من أعماله وحمايتها من مختلف أنواع الاعتداء. غير أنها وإن كانت تتشابه في البعض منها مع الحقوق المخولة للمؤلف لحماية مصنفات ه وشخصه، إلا أنها تختلف معها في البعض منها لاسيما الحق في تقرير النشر، والحق في السحب أو الندم، باعتبار أن التشريعات الوطنية الخاصة بالحقوق المجاورة والتي اعترف ت للفنان التمتّع بحق معنوي ، جاءت خالية من الإشارة إلى ذلك. لذا كان من الضروري تحديد مدى تمتع الفنان العازف بهذين الحقين، أمام الف ا رغ القانوني الذي أدى إلى مجادلات فقهية وتضا رب في الأحكام القضائية. L'artiste interprète ou exécutant est le seul des titulaires de droits voisins à bénéficier d’un droit moral et d’un droit patrimonial sur son interprétation. Le caractère original de sa prestation met en valeur sa personnalité littéraire et artistique, à l’inverse des oeuvres des titulaires de droits voisins qui se caractérisent par leur aspect industriel et matériel. Le droit moral dont dispose l'artiste-interprète, comprend un ensemble de prérogatives qui lui permettent de bénéficier de ses oeuvres et de les protéger contre les divers abus. Cependant, et bien qu’elles soient similaires, pour certaines d’entre elles, aux droits octroyés à l’auteur pour protéger son oeuvre et sa personne, elles se différencient de certains d’entre eux, en particulier le droit de divulgation et le droit de retrait ou de repentir, du fait que les législations nationales relatives aux droits voisins qui reconnaissent à l'artiste la jouissance d’un droit moral, sont dépourvues de toute référence à ce sujet. Dès lors, il était nécessaire de déterminer dans quelle mesure l'artiste-interprète jouit de ses deux droits, face au vide juridique qui a donné lieu à des controverses doctrinales et à des décisions de justice contradictoires. The artist, musician or performer, is the only one of the holders of related rights to benefit from a moral right and financial rights over his performance. The original character of his performance highlights his literary and artistic personality, unlike the works of holders of neighboring rights which are characterized by their industrial and material aspect. The moral rights available to the performer include a set of prerogatives that allow them to benefit from their works and protect them against various abuses. However, and although they are similar, for some of them, to the rights granted to the author to protect his work and his person, they are different from some of them, in particular the right of disclosure and the right of withdrawal or of repentance, due to the fact that national laws relating to neighboring rights which recognize the artist's enjoyment of a moral right, are devoid of any reference to this subject, Therefore, it was necessary to determine to what extent the performer enjoys both rights, in the face of the legal vacuum which has given rise to doctrinal controversies and contradictory court decisions.
Keywords: Arbitrage; Arbitration; Artist interpréter; Artist performer; Artiste exécutant; Artiste interprète; Contrefaçon; Counterfeiting; Droit moral; Intellectual property; International protection; Moral right; National protection; Piracy; Piratage; Propriedade intelectual; Propriété intellectuelle; Protection internationale; Protection nationale; Responsabilité; Responsibility

ال رقابة القضائية على أحكام ال ت حكيم دراسة مقارنة في القوانين العربية - زريفي, محمد (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
إن كان التحكيم طريقا بديلا للقضاء في حسم المنازعات، فإن عملية التحكيم تحتاج لكي تكتمل أسباب فاعليتها وانفاذ أحكامها لتدخل قضاء الدولة باعتباره سلطة عامة، تملك قوة إل ا زم الخصوم بتنفيذ أحكام المحكمين. ومن باب المفارقة، أن هذه الرقابة القضائية على أحكام التحكيم، تؤدي إلى إقحام القاضي الوطني في ن ا زع، أستبعد منه مسبقا بإ ا ردة المتنازعين، إلا أن المفارقة ظاهرية، حيث أن دور القاضي يبقى منحص ا ر في رقابة مدى مطابقة الحكم التحكيميي لمبادئ أساسية، أتت على سبيل الحصر، دون أن يكون له فحص وقائع وموضوع الن ا زع. غير أن تحديد سلطة القاضي لي س مطلقة، فبناء على المقاربة الجديدة المبنية على نوع المصالح المطلوب حمايتها، كمعيار لتحديد درجة وشدة الرقابة المسلطة على حكم لتحكيم، يستطيع هذا الأخير، تعديل رقابته بين مشددة ومخففة . وعلى هذا الأساس، فإن غالبية القضاءات العربية تبنت موقفا وسطيا بين مذهبي التوسع والتضييق من نطاق رقابة المحاكم على حكم التحكيم الدولي، تماشيا مع متطلبات التجارة الدولية ومقتضيات مصالحها الوطنية . If arbitration is an alternative means of resolving disputes, the arbitration process needs, for the reasons of its effectiveness and the application of its provisions, the intervention of the judicial power of the State, in order to oblige the parties to carry out the arbitral awards. Paradoxically, this judicial review of arbitral awards leads to involving the national judge in a dispute, which was previously excluded by the will of the parties in dispute. However, this paradox is apparent, because the role of the national judge remains limited to the strict control of the compliance of the arbitration award with the basic principles enacted in an exclusive manner, without having to examine the facts and the subject of the dispute. However, this limitation of judicial power is not absolute, because on the basis of the new approach, based on the type of interests to be protected, as the criterion for determining the extent of the control exercised over an arbitral award, the latter can modulate its control between strict and attenuating. On this basis, the majority of Arab jurisdictions have adopted a middle position between the two tendencies, so-called maximalist control, and minimalist tendency of the jurisdictions' control over the international arbitration award, in accordance with the needs of international trade and the requirements of their interests. Si l'arbitrage est un moyen alternatif pour de résoudre les différends, le processus d'arbitrage a besoin, pour les raisons de son efficacité et l'application de ses dispositions de l'intervention du pouvoir judiciaire de l'État, afin d'obliger les parties d'exécuter les sentences arbitrales. Paradoxalement, ce contrôle judiciaire sur les sentences arbitrales conduit à impliquer le juge national dans un litige, qui en était auparavant exclu par la volonté des parties en litige. Toutefois, ce paradoxe est apparent, car le rôle du juge national reste limité au strict contrôle de la conformité la sentence arbitrale aux principes de base édicté d’une manière exclusive, sans avoir à examiner les faits et l'objet du litige. Cependant, cette limitation de pouvoir juge n'est pas absolue, car sur la base de la nouvelle approche, fondée sur le type d'intérêts à protéger, comme critère de détermination de l'étendue du contrôle exercé sur une sentence arbitrale, ce dernier peut moduler son contrôle entre strict et atténuant. Sur cette base, la majorité des juridictions arabes ont adopté une position médiane entre les deux tendances, contrôle dite maximaliste, et tendance minimaliste du contrôle des juridictions sur la sentence d'arbitrage international, conformément aux besoins du commerce international et aux exigences de leurs intérêts.
Keywords: Arbitrage international; Arbitration; Commerce international; Contrôle des juridictions; International Trade; International arbitration award; Sentence arbitrale

Capacity of the International Investment Arbitration Mechanism in Environmental Protection - Habibi Majandeh, Mohammad; Gholami, Afife (Public Law Researsh, 2021)
Environmental considerations have always been a challenge for foreign investment. The need to observe environmental minimums from the beginning to the end of the investment is also a concern of environmental law activists. In the meantime, the host state faces sometimes conflicting commitments. State dual obligations to foreign investors on the one hand, and the whole citizens on the other, has in many cases led to disputes, rooted in environmental norms. The main question is how the arbitration mechanism can take an active stand in the face of such disputes? The main purpose of this study is to examine the reflection of these conflicts in investment arbitration and the importance and role of arbitration in improving the environmental status. The authors of this paper believe that the arbitration system has tools that it can use in resolving disputes to balance these conflicting obligations. Some of these legal tools are directly or indirectly related to investment agreements, and others are beyond the treaty and based on international principles, rules, customs and practices. ملاحظات محیط زیستی همواره یکی از چالش های پیشروی سرمایه گذاری خارجی بوده است. لزوم رعایت حداقل های زیست‌محیطی از آغاز تا پایان سرمایه گذاری، از دغدغه های فعالان حوزه حقوق محیط زیست نیز می باشد. در این میان دولت میزبان با تعهداتی بعضاً متعارض روبروست. تعهدات دوگانه دولت در برابر سرمایه گذار از یک طرف و عموم شهروندان از طرف دیگر، در موارد متعددی به بروز اختلافاتی منجر شده که ریشه در هنجارهای محیط زیستی دارد. پرسش اصلی این است که سازوکار داوری در مواجهه با این نوع اختلافات، چگونه می تواند فعالانه موضع گیری نمایند؟ هدف اصلی این مطالعه بررسی بازتاب تعارض ها در رویه داوری سرمایه گذاری و اهمیت و نقش داوری در بهبود وضعیت محیط زیستی است. نویسندگان این نوشتار بر این باورند که سیستم داوری، ابزارهایی در اختیار دارد که می تواند از آنها در جریان حل اختلاف برای ایجاد تعادل میان این تعهدات متعارض استفاده کند. برخی از این ابزارهای حقوقی مستقیم یا غیرمستقیم با معاهدات سرمایه‌گذاری مرتبط است و دستهای دیگر فرامعاهده ای و ناشی از اصول، قواعد، عرف ها و رویه های بین المللی است.
Keywords: Arbitrage; Arbitragem; Arbitration; Bilateral Treaties; Environmental Protection; International Arbitration; Investment Disputes; Legal Instruments; ابزار حقوقی; اختلافات سرمایه‌گذاری; حمایت از محیط ‌زیست; داوری بین‌المللی; معاهدات دوجانبه

مراكز التحكيم البحري - بلقاسم, حبيب (Université d'Oran 2 Mohamed Ben Ahmed, 2021)
"Les centres d’arbitrage maritime." Résumé : Le sujet des centres d'arbitrage maritime concerne le processus de résolution des contentieux maritimes quand leurs parties optent pour soumettre leur différend à des instances d'arbitrage comme voie alternative. Les centres d'arbitrage maritime appliquent le règlement arbitral et ses règles dans le cas où le choix est fait en fonction de la clause compromissoire qui inclut ce choix ainsi que la loi applicable. Lacompétence de cet instance d'arbitrage convenue débute à la date de la soumission de la demande d'arbitrage, afin de lui confier le suivi des procédures d'arbitrage et de tout ce qui touche au litige arbitral et jusqu' à ce que la sentence (décision) arbitrale soit rendue. "Maritime arbitration centers." Summary: The subject of maritime arbitration centers concerns the process of resolving maritime disputes when their parties opt to submit their dispute to the arbitral tribunal as an alternative solution, and maritime arbitration centers apply arbitration regulations and its rules in case where the choice is made according to the arbitration clause which includes this choice as well as applying the law on all disputes. The arbitral tribunal function starts from the date of submitting the arbitration request to it to be entrusted with following up the arbitration procedures and everything related to the arbitration dispute and until the arbitral award is issued. : الملخص يتعلق موضوع مراكز التحكيم البحري بعملية فض المنازعات البحرية التي يختار أطرافها عرض النزاع على هيئات التحكيم كطريق بديل، و مراكز التحكيم البحري تعمل على تطبيق لوائح التحكيم و نظامها التحكيمي في حال وقوع الاختيار عليها وفقا لشرط التحكيم الذي يتضمن هذا الاختيار، إلى جانب القانون الواجب التطبيق على النزاع. و يبدأ اختصاص هذه الهيئة في التحكيم المؤسسي من تاريخ تقديم طلب التحكيم إليها، ليوكل لها متابعة إجراءات التحكيم و كل ما يتعلق بالمنازعة التحكيمية و إلى غاية صدور الحكم التحكيمي.
Keywords: Application for arbitration; Arbitral Awards; Arbitration; Centres d'arbitrage maritime; Clause d'arbitrage maritime; Demande d'arbitrage; Décision d'arbitrage; Maritime arbitration centres; Maritime arbitration clause

رقابة القضاء على أعمال المحكمين - غزيزات, دليلة (Université d'Oran 2 Mohamed Ben Ahmed, 2021)
رقابة القضاء على أعمال المحكمين من بين أوجه الرقابة التي أقرتها التشريعات الحديثة وقوانين التحكيم الوطنية و الإتفاقيات الدولية وكذا نظام التحكيم في ظل تطور الثقافة التحكيمية في الوقت الراهن. كما تعد ضمانا وحماية للمصالح وحقوق الأفراد والشركات التجارية من جهة وتُمكن القضاء من السيطرة على تصرفات المحكمين وحماية شخصهم في الدعوى التحكيمية لتحقيق فاعلية نظام التحكيم من جهة ثانية. Le contrôle des actes des arbitres est établi par les législations récentes et par la législation arbitrale nationale, ainsi que par les conventions internationales en la matière. Il participe à l’évolution de la culture arbitrale et constitue une garantie et une protection des intérêts des individus et des sociétés commerciales. Il permet d’avoir une vue sur les travaux des arbitres d’une part, et sur leur protection d’autre part, pour assurer l’efficacité de l’arbitrage. The review of the acts of the arbitrators shall be established by recent laws and national arbitral legislation and international conventions on the subject. It contributes to the evolution of the arbitral culture and constitutes a guarantee and protection of the interests of individuals and commercial company’s .It allows having a view on the work of the arbitrators on the one hand, and on their protection to ensure the effectiveness of arbitration
Keywords: Arbitral proceedings; Arbitration; Arbitrator; Arbitre; Contrôle; Judge; Juge; Procédure arbitrale

التحكيم رديفاً للقضاء في حل المنازعات - دراسة فقهية - Abu Lail, Mohammad (Jordan Journal of Islamic Studies, 2020)
Arbitration is considered as one of the basic means that has been legislated by Islam to resolve the people's disputes. Usually the resolutions of the arbitration are fast, guarantee the rights, respect the essence of justice and reduce the level of the controversy. Today, arbitration plays a vital role in resolving the international disputes such as the economic, political and local disputes as long as its effect upon the resolution of the internal disputes. This study highlights on the arbitration role in resolving the disputes as along with judiciary through showing the advantages of the arbitration and explain the relationship between arbitration and judiciary. And clarify its areas and its implications in jurisprudence. This study found out that the arbitration has a pivotal role in resolving the disputes resulting from the contractual and non-contractual relationships and the disputes resulting from the people in their natural and moral capacity, both internally as well as externally The study has shown the jurisprudence has taken the lead in explaining the terms and effects of the arbitration.

الاطار القانوني للاستثمار العربي في الجزائر - عبد الصدوق, حفيظة (Université d'Oran 2 Mohamed Ben Ahmed, 2018)
للاستثمار العربي في الج ا زئر أهمية خاصة لسببين: أحدهما يتعلق بأهمية الاستثمار في حد ذاته لما يلعبه من دور لا يستهان به في التنمية الاقتصادية للدولة، مؤث ا ر على كل جوانب الحياة في المجتمع بما يوفره من تطور اقتصادي وازدهار واستق ا رر، وثانيهما يرتبط باتخاذه وسيلة لتجسيد التعاون العربي المشترك وتحقيق التكامل المنشود منذ عقود، والذي تأكد عدم تحققه الا بالاعتماد على المدخل الإنتاجي من خلال توظيف رؤوس الأموال العربية في الدول العربية. بدافع هذين العاملين وجذبا لرؤوس الأموال العربية وضعت الج ا زئر اطا ا ر قانونيا ا زخ ا ر بالضمانات والامتيا ا زت بعد تحديد مفهوم الاستثمار العربي، هذا الإطار يتألف من الاحكام الاتفاقية السامية على التشريع الوطني الواردة في الاتفاقيات المبرمة بين الج ا زئر والدول العربية بعد المصادقة عليها، ومن احكام التشريع الوطني الذي يعد آلية قانونية تنفذ بها الدولة است ا رتيجياتها. ت ا زمن ذلك مع تهيئة مناخ الاستثمار بصفة عامة من خلال الإصلاحات التي طالت مختلف التشريعات المتعلقة بإقامة الاعمال اولاستثمار في الج ا زئر. جاءت هذه الد ا رسة لتبين معالم هذا الإطار القانوني، مكوناته ومدى تأثيره في رفع مست وى الاستثمار العربي في الج ا زئر كما ونوعا، ضمن مشاريع التكتل الإقليمي والجهوي او المبادلات الثنائية مع الدول العربية.
Keywords: Accords bilatéraux; Algeria; Arab Nationality; Arbitrage; Arbitration; Bilateral Agreements; Blocage; Blocking; Business Establishment; Compensation; Création d'entreprise; Encouragement; Garanties; Guarantees; Investissements; Investment Protection; Investments; Nationalité arabe; Privileges; Privilèges; Protection des investissements

فعالية اتفاق التحكيم التجاري الدولي - تعويلت, كريم (جامعة مولود معمري, 2017)
استند الفقه والقضاء على فكرة فعالية اتفاق التحكيم مجال التجارة الدولية، لتبرير الأخذ ببعض القواعد، كاستقلالية هذا الاتفاق ومبدأ "الاختصاص بالاختصاص"، التي كيفت على أنها قواعد مادية ومبادئ راسخة في قانون التحكيم التجاري الدولي. غير أن اللجوء إلى هذه المبادئ في مفهومها الليبرالي الحالي ، الذي وصل إليه خاصة القانون الفرنسي ، يسمح من الناحية العملية بانفلات هذا الاتفاق ليس فقط من حكم القانون الوطني، بل أيضا من إرادة الأطراف، التي جاءت هذه المبادئ لحمايتها، لذا نرى أنه من الأجدر الأخذ بالحلول التي وضعها القانون النموذجي للتحكيم التجاري الدولي، الذي سنته لجنة الأمم المتحدة للقانون التجاري الدولي في سنة 1985. L’efficacité de la convention d’arbitrage en matière de commerce international a été évoquée pour justifier le recours à certaines règles telles que l’autonomie de ladite convention et la « compétence-compétence ». Ces dernières sont qualifiées de règles matérielles et de principes indiscutables du droit de l’arbitrage international. Toutefois, le recours à ces principes dans leur sens actuel permet en pratique, et selon la conception du droit français notamment, de soustraire la convention d’arbitrage non seulement à toute loi étatique, mais aussi à la volonté des parties que ces principes sont sensés préserver. Par conséquent, nous pensons qu’il est préférable de recourir aux solutions consacrées par la loi type sur l’arbitrage commercial international de la CNUDCI de 1985
Keywords: Arbitrage; Arbitrage commercial international; Arbitration; Commerce international; Compétence-compétence; Convention d'arbitrage; اتفاق التحكيم; التجارة الدولية; التحكيم التجاري الدولي; مبدأ الإختصاص بالإختصاص

دور المحكم في الخصومة التحكيمية - حمودي, سمية (جامعة الوادي university el-oued, 2016)
تناولت هذه الدراسة أهم عنصر من عناصر عملية التحكيم، ألا وهو دور المحكم في خصومة التحكيم، وذلك من خلال معرفة شروط وإجراءات اختاره ومركزه القانوني وسلطاته والتزاماته . و قد بدأت الدراسة بمقدمة تضمنت العناصر الرئيسية للبحث وتناولنا ف الفصل الأول التعريف بالمحكم من خلال بيان معناه وتميزه عن القاضي والخبير والمصالح والوكيل، كذلك بيان الشروط الواجب توافرها في المحكم، كما تم توضيح المركز القانوني للمحكم في خصومة التحكم وكذا بيان طرق تشكيل هيئة التحكيم. كما تناولنا سلطات المحكم، سواء كانت ناشئة عن اتفاق التحكيم، أم المخولة له بموجب القانون، وبيان الالتزامات المرمية على عاتقه أثناء مباشرته لمهمته، وكل ذلك من خلال الفصل الثاني. ومن أهم النتائج التي خلصت إليها الدراسة، هي أن المحكم يتمتع بسلطات واسعة في خصومة التحكيم، إلا أن هذه السلطات الواسعة ليست مطلقة بلا قيود، وإنما يفرض على المحكم عدة التزامات منذ قبوله مهمة التحكيم وحتى صدور الحكم الفاصل في النزاع مرورا بالتزاماته أثناء سير الاجراءات مع مراعاة احترام المبادئ الأساسية للتقاضي. Cette étude portait sur l'élément le plus important du processus d'arbitrage, à savoir le rôle d'arbitre dans l'arbitrage des différends, et grâce à la connaissance des conditions et des procédures choisies statut juridique, pouvoirs et obligations. L'étude a commencé par une introduction comprenait les principaux éléments de la recherche et nous traitée dans le premier arbitre de définition de chapitre à travers les moyens de déclaration et de le distinguer du juge et expert, des intérêts et de l'agent, ainsi que la déclaration des conditions à remplir par l'arbitre, a également clarifier le statut juridique d'un arbitre dans le contrôle des différends, ainsi qu'une description des moyens de la formation du tribunal. Comme nous approchions les autorités de l'arbitre, que ce soit en raison de la convention d'arbitrage, ou qui lui sont conférés en vertu de la loi, et la déclaration des obligations jetées sur lui-même pendant l'exécution de leur mission, et tout au long du deuxième trimestre. Parmi les résultats les plus importants de l'étude, il est que l'arbitre dispose de larges pouvoirs à l'arbitrage des différends, mais ces larges pouvoirs est pas absolue, sans restrictions, mais a imposé à l'arbitre plusieurs engagements depuis accepter la tâche d'arbitrage et jusqu'à la délivrance de l'arbitre décisif dans le conflit par ses obligations au cours de la procédure, avec en tenant compte du respect des principes de base du litige
Keywords: Arbitrage des différends; Arbitration; Arbitre; Obligations de l'arbitre; Pouvoirs de l'arbitre; Statut juridique; Tribunal arbitral; التزامات المحكم; الخصومة التحكيمية; المحكم; المركز القانوني; سلطات و; هيئة التحكيم